Implementation of Project-Based Assessment to Assess the Students’ Speaking Skills in Vocational High School - Eka Putri Dea Ayu Maharani; Januarius Mujiyanto; Sri Wahyuni (English Education Journal, 2024)
Business and industry leaders are emphasizing the need for future employees to possess strong industry skills and, crucially, to communicate effectively in English to engage with international markets. This has led to a call for an assessment approach in vocational education that promotes higher-order thinking skills instead of just rote memorization and factual recall in English language instruction. Project-Based Assessment (PBA) is a key method in vocational education reform, engages various stakeholders through authentic tasks showcasing students' knowledge and skills. This study uses an explanatory sequential design to explore Project-Based Assessment's implementation in improving speaking skills at SMK Wisudha Karya Kudus, examining teacher and 70 students’ perception and its impact on motivation and skill enhancement. The findings of this study reveal that PBA had been implemented by the teacher since 2021 as it helped the teacher to find out some aspects of students’ skill by using one project. Out of 2 classes consists 70 students indicate a positive development in the performance both classes, reflecting a slight improvement in their skills. Though time management and English habitual became the obstacles in the implementation of this assessment approach, through motivation and positive feedback, the teacher is still able to help the students increasing their speaking skills.